Haemostatic profiles assessed by thromboelastography in patients with end-stage renal disease - Darlington, Andrew; Luis Ferreiro, Josè; Ueno, Masafumi; Suzuki, Yoshi; Desai, Bhaloo; Capranzano, Piera; Capodanno, Davide; Tello-Montoliu, Antonio; Bass, Theodore A.; Nahman Norris, S; Angiolillo, Dominick J. (Thrombosis and Haemostasis, 2011)
Patients with end-stage renal disease (ESRD) have abnormalities in the cellular and plasmatic systems regulating blood homeostasis, which may contribute to their risk for thrombotic and bleeding complications. However, their relative contributions in this population are poorly understood. The aim of this study was to evaluate the distribution of enzymatic and cellular abnormalities in ESRD patients on haemodialysis as assessed by thromboelastography (TEG®). Whole blood samples were analysed by TEG in ESRD patients (n=70) and in a control group (n=70) of subjects with coronary artery disease. Profiles were constructed considering the maximum amplitude (MA), a marker of platelet function, and reaction time (R), a marker of thrombin generation, values. R values were higher in ESRD patients compared with the control group (8.2 ± 2.8 vs. 5.7 ± 1.9 minutes [min], p <0.0001), while there were no differences in MA (66.7 ± 8.1 vs. 66.2 ± 6.6 mm, p=0.562). Nor mal manufacturer defined coagulation (2–8 min) and aggregation (51–69 mm) parameters were present in 31% of ESRD patients compared with 56% of controls (p=0.006). A hypocoagulable status was observed in 42.9% of ESRD patients compared with 8.9% in the control group (p<0.0001). There were no differences in platelet function, which showed a hyperaggregable status in 41.4% versus 35.7% of cases (p=0.603). Abnormalities in both parameters were observed in 15.7% of ESRD patients versus 1.4% in the control group (p = 0.004), which were more common among older patients (p= 0.005). In conclusion, patients with ESRD have an elevated prevalence of abnormal haemostatic profiles, which may contribute to their elevated risk of bleeding and thrombotic complications.
Keywords: End stage renal disease; platelet function; coagulation